EXPANSION AND MODERNIZATION OF POSTAL SERVICES IN SANTA CATARINA (1930–1945) (Revista de História Regional, 2025)
We can observe that in Brazil, and by extension in Santa Catarina, during the years 1930 to 1945, there was a restrictive expansion and localized modernization of postal services. It was restrictive because there was growth in postal activity, combining periods of contraction and expansion, and localized because we observe advancements in certain services (airmail and the construction of new headquarters). Both restrictive expansion and localized modernization are associated with economic performance and state modernization. In this article, we will analyze these two movements in postal services in Santa Catarina, which are combined to enable the expansion and modernization of the postal system.
Keywords: postal services; modernization; Santa Catarina; state